Cinderella Reading with Phonics - Page; Nick (China Make Believe Ideas)
A fun retelling of the story of Cinderella. Share the story and the learning activities with your child to encourage their reading and reinforce their learning of phonics. The story is told in a lively, rhyming text with a key sound targeted. Letters are highlighted in red to help children focus on the different groups of letters that make this sound. Young children aged 4+ learning to read with phonics. This particular example focuses on the key sound 'ow' with 'ow, ou, th, ll and wh'. This hardback book has 32 pages and measures approximately: 17.6 x 11.6 x 0.8cm.